Respuesta :

Answer:  The required product is [tex]8y^3+6y^2-29y+15.[/tex]

Step-by-step explanation:  We are given to find the following product :

[tex]P=(4y-3)(2y^2+3y-5).[/tex]

To find the given product, we need to multiply each term of the first expression to each term of the second expression.

The multiplication is as follows :

[tex]P\\\\=(4y-3)(2y^2+3y-5)\\\\=4y(2y^2+3y-5)-3(2y^2+3y-5)\\\\=8y^3+12y^2-20y-6y^2-9y+15\\\\=8y^3+6y^2-29y+15.[/tex]

Thus, the required product is [tex]8y^3+6y^2-29y+15.[/tex]

ACCESS MORE